Effect of rapid weight loss on mood states and burnout of Brazilian jiu-jitsu athletes during a competitive process - Bueno, João Carlos Alves; Silva, Rodrigo Batalha; Diotaiuti, Pierluigi; Andreato, Leonardo Vidal; Andrade, Alexandro (Frontiers in Psychology, 2023)
The current study aimed to analyze the psychological alterations resulting from rapid weight loss in the mood states and burnout of male Brazilian jiu-jitsu athletes. For the purpose of this study, 31 Brazilian jiu-jitsu athletes participated, divided into two groups (RWLG: rapid weight loss group and CG: control group). Data collections were performed at three moments (1: baseline, before weight loss; 2: weigh-in, during the official competition; and 3: recovery, 7 to 10 days after the competition), with application of the Brunel Mood Scale (BRUMS) and Athlete Burnout Questionnaire (ABQ). Considering the outcomes, for body mass, the athletes from RWLG presented mean reductions of 3.5 kg (4.2% of the initial body mass). For mood states, both groups (RWLG and CG) presented a moment effect for tension and confusion, with higher levels during weigh-in compared to baseline and recovery (p < 0.05). For burnout, both groups showed low levels of burnout, with no effect of moment, group, or interaction in the analyses (p > 0.05). Based on these results, it is concluded that weight loss, in the magnitude performed in this study, did not generate an additional impact on mood or level of burnout in Brazilian jiu-jitsu athletes during a competitive process.